Kompres Serai Hangat Dapat Menurunkan Nyeri Akut Gout Arthritis: Studi Kasus - Ahmad Zaini Arif; Sulaiman Rofiki; Yunita Amilia (Indonesian Health Science Journal, 2023)
Introduction: Gout Arthritis or commonly referred to as gout is an inflammatory disease of the joints that can cause pain, heat, swelling, and stiffness in the joints caused by excess uric acid content in the blood resulting in accumulation of uric acid crystals in the joints and soft tissues other. Non-pharmacological therapy that can be done is giving warm compresses of lemongrass boiled water. Method: This study uses the case study method. The subjects used were 2 people with a medical diagnosis of Gout Arthritis. The instrument for collecting data used a questionnaire and NRS. Results: The results of the application show that after giving lemongrass warm compresses 1 time a day for 3 days within 20 minutes each administration the pain scale decreases or even disappears when evaluated on the third day where in the first patient before the pain scale intervention was 6 and after the pain scale intervention to 0 while the second patient before the intervention had a pain scale of 6 and after the intervention had a pain scale of 2. Conclusion: Warm compresses of lemongrass boiled water can reduce acute pain in Gout Arthritis patients.